2016
DOI: 10.3389/fmicb.2016.00646
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the N-Acylhomoserine Lactone-Degrading Bacterium Alteromonas stellipolaris PQQ-42 and of Its Potential for Biocontrol in Aquaculture

Abstract: The production of virulence factors by many pathogenic microorganisms depends on the intercellular communication system called quorum sensing, which involves the production and release of signal molecules known as autoinducers. Based on this, new-therapeutic strategies have emerged for the treatment of a variety of infections, such as the enzymatic degradation of signaling molecules, known as quorum quenching (QQ). In this study, we present the screening of QQ activity amongst 450 strains isolated from a bival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 85 publications
5
80
0
Order By: Relevance
“…QQ activity of Staphylococcus sp. strain EN21 for AHL degradation was analysed using a well diffusion agar-plate assay [42,43]. Briefly, each synthetic AHL in a final concentration of 25 µM was added to overnight cultures of strain EN21 and then incubated at 28 • C for 24 h. Cell-free TSB medium supplemented with the same concentration of AHLs was incubated as negative control.…”
Section: Quorum Quenching Activity Against Synthetic Ahls and Crude Amentioning
confidence: 99%
See 1 more Smart Citation
“…QQ activity of Staphylococcus sp. strain EN21 for AHL degradation was analysed using a well diffusion agar-plate assay [42,43]. Briefly, each synthetic AHL in a final concentration of 25 µM was added to overnight cultures of strain EN21 and then incubated at 28 • C for 24 h. Cell-free TSB medium supplemented with the same concentration of AHLs was incubated as negative control.…”
Section: Quorum Quenching Activity Against Synthetic Ahls and Crude Amentioning
confidence: 99%
“…Co-culture assays of plant bacterial pathogens and strain EN21 were carried out according to the methodology described by Torres et al [43]. Briefly, 10 9 CFU mL −1 of each pathogenic strain was co-cultured with 10 9 CFU mL −1 of strain EN21 (1:100) in TSB medium at 28 • C and 150 rpm for 24 h. A similar concentration of each pathogen was added to cell-free TSB medium as negative control.…”
Section: Phytopathogens Qs System Interference By Co-culture Assaysmentioning
confidence: 99%
“…The pioneer studies on the ecological relevance of QQ processes carried out with bacteria isolated from soil and rhizosphere indicated that 2–4.8% of these strains had the ability to interfere with AHLs [ 42 , 43 , 44 ]. More recent studies revealed a high prevalence of QQ enzymes in the marine environment: enzymatic QQ activity was observed in bacterial strains isolated from corals [ 23 , 45 ], sponges [ 46 ], marine biofilms [ 47 ], estuarine and open ocean superficial seawater [ 48 , 49 ], and fish and bivalve hatcheries [ 50 , 51 ], presenting higher frequencies of bacteria with this capability (2–46%) in comparison to terrestrial samples [ 46 , 48 , 52 , 53 , 54 ]. The importance of QQ processes in the marine environment was further supported by metagenomic studies showing a high frequency of QQ enzymes in marine metagenomic collections including the Global Ocean Sampling collection [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Application of AHL degrading bacteria able to utilize AHL molecules of marine and freshwater pathogens as a food source is a developing idea due to their previously successful outcomes [17][18][19][20][21][22]. However, the majority of the strains that have been tested in the past are allochthonous QQ bacteria [21,23].…”
Section: Introductionmentioning
confidence: 99%
“…Application of AHL degrading bacteria able to utilize AHL molecules of marine and freshwater pathogens as a food source is a developing idea due to their previously successful outcomes [17][18][19][20][21][22]. However, the majority of the strains that have been tested in the past are allochthonous QQ bacteria [21,23]. Moreover, the isolation of autochthonous bacteria with QQ potential has frequently been reported from freshwater fish [19,[24][25][26], and to our knowledge, there is only one report in marine fish [27].…”
Section: Introductionmentioning
confidence: 99%